Present and future of antiarrhythmic therapy for atrial fibrillation: A review - Aida I. Tarzimanova (ZAO "Consilium Medicum", 2024)
Despite the emergence and active development of interventional methods for the treatment of arrhythmias, to date, the use of antiarrhythmic drugs to recover and maintain sinus rhythm is the most significant and in demand in patients with paroxysmal and persistent forms of atrial fibrillation (AF). The results of multicenter randomized clinical studies show that early antiarrhythmic therapy to recover and maintain sinus rhythm improves the prognosis for patients with AF. Currently, the most effective and safe drugs to control AF paroxysms and maintain sinus rhythm are class 1C and III agents, according to the Vaughan-Williams classification. The development of new antiarrhythmic drugs brings hope for the emergence of an effective and safe means for the control and prevention of AF, which will significantly improve the quality of life of patients and their prognosis.